Hyaluronan in cancer – from the naked mole rat to nanoparticle therapy. Issue 17 (15th April 2016) - Rankin, Kenneth S.; Frankel, Daniel
Abstract : Hyaluronan, a biopolymer abundant in the tumour microenvironment plays an important role in cancer. Its soft matter properties deserve detailed consideration. Abstract : Hyaluronan, a glycosaminoglycan, abundant in the tumour microenvironment, is a key player in many processes associated with cancer. Recently the cancer resistance of the naked mole rat has been attributed to the presence of an ultra-high molecular weight form of this molecule. The physical properties of this multifunctional biopolymer have been extensively studied in the context of synovial joints. However, relatively little has been reported with regard to the soft matter properties of hyaluronan in relation to cancer. In this review we examine the role of hyaluronan in cancer, paying particular attention to its mechanical interactions with malignant cells and its soft matter properties. In addition we discuss the use of hyaluronan based gels to study cancer invasion as well as nanoparticle based strategies for disease treatment.